Atmospheric Pressure Radio Frequency Dielectric Barrier Discharges in Nitrogen/Argon - 刘忠伟 杨丽珍 王正铎 桑利军 朱强 李森 (Plasma science & technology, 2013)
This work reports the experimental results on the characteristics of radio frequency dielectric barrier N2/Ar discharges. Depending on the nitrogen content in the feed gas and the input power, the discharge can operate in two different modes： a homogeneous glow discharge and a constricted discharge. With increasing input power, the number of discharge columns increases. The discharge columns have starlike structures and exhibit symmetric self-organized arrangement. Optical emission spectroscopy was performed to estimate the plasma temperature. Spatially resolved gas temperature measurements, determined from NO emission rotational spectroscopy were taken across the 4.4 mm gap filled by the discharge. Gas temperature in the middle of the gas gap is lower than that close to the electrodes.